2021
DOI: 10.5005/ejp-13-1--2-25
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Thyroid Hormone Levels among the Normal Healthy Persons, Depression and Schizophrenia

Abstract: Background: Thyroid disorders can induce virtually any psychiatric symptom or syndrome, although no consistent associations of specific syndromes and thyroid conditions are found. Abnormal thyroid hormone levels are common in psychiatric disorders Material & Method: T3, T 4 , TSH levels were measured in a sample of 90 (ninety) cases who attended Department of Psychiatry, RIMS hospital. The sample consists 30 (thirty) cases each from three-group viz., Controls consisting of normal healthy persons, Schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, significantly low levels of serum T3 were found in cases compared to controls. Low levels of T3 in schizophrenia patients were also reported by Polat et al [31], whereas the opposite result was reported by Singh et al [41].…”
Section: Discussionmentioning
confidence: 60%
“…However, significantly low levels of serum T3 were found in cases compared to controls. Low levels of T3 in schizophrenia patients were also reported by Polat et al [31], whereas the opposite result was reported by Singh et al [41].…”
Section: Discussionmentioning
confidence: 60%